Decolonizing Higher Education: Historical Myths, Official Discourses, and University Reforms in Brazil - de Almeida-Filho, Naomar (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2023)
From a decolonial perspective, I propose in this paper a critical assessment of the university in Latin America as a social institution which, to fulfill its historical mission, needs to continuously recreate its institutional identity considering subaltern and peripheral economic, political and ideological contexts of coloniality. First, I provide a very brief account of the decolonial thought and its notions of ‘coloniality of power’, ‘coloniality of knowledge’ and ‘coloniality of being’. Secondly, in addition to revisiting historical grand narratives, I present a very brief history of higher education reforms in the Western world, followed by some highlights on the history of university reforms in Brazil. Then I introduce three index-cases of coloniality related to the Brazilian university to illustrate the topic. The first one I call the denial of Georges Cabanis, the second one has been called by historians as the Humboldt Myth, and the third one is a strong statement of my own responsibility: we Brazilians have never been Flexnerians. The specific discussion on how to interpret these emblematic index-cases of coloniality are my closing remarks for opening further debates on strategies and actions for decolonizing the University.